Seduction of Ethics : Transforming the Social Sciences - Van den Hoonaard, Will. C. (Willy Carl), 1942- (Book collections on Project MUSE., 2011)
Formal research-ethics committees in Canada now function as an industry, costing over thirty-five million dollars annually. The Seduction of Ethics argues that while ethics codes are alluring to the public, they fuel moral panic and increase demands for institutional accountability. Will C. van den Hoonaard explores the research-ethics review process itself by analysing the moral cosmology and practices of ethics committees regarding research and researchers. The Seduction of Ethics also investigates how researchers have tailored their approaches in response to technical demands - leading social science disciplines to resemble each other more closely and lose the richness of their research. Van den Hoonaard reveals an idiosyncratic and inconsistent world in which researchers employ particular strategies of avoidance or partial or full compliance as they seek approval from ethics committees.